2007
DOI: 10.1073/pnas.0708600104
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the mechanistic roles of enzyme conformational dynamics

Abstract: Many enzymes mold their structures to enclose substrates in their active sites such that conformational remodeling may be required during each catalytic cycle. In adenylate kinase (AK), this involves a large-amplitude rearrangement of the enzyme's lid domain. Using our method of high-resolution single-molecule FRET, we directly followed AK's domain movements on its catalytic time scale. To quantitatively measure the enzyme's entire conformational distribution, we have applied maximum entropy-based methods to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
430
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(480 citation statements)
references
References 48 publications
41
430
5
Order By: Relevance
“…Adk undergoes a large conformational change in response to ligand binding that shuttles the protein into a closed and active conformation where phosphoryl transfer occurs (Rhoads & Lowenstein, 1968). Because of its favorable properties -specifically, its tendency to yield excellent NMR spectra (Ådén & Wolf-Watz, 2007;Schrank et al 2009), catalysis of a reversible reaction, and large conformational changes (Müller et al 1996;Müller & Schulz, 1992) -Adk has emerged as one of the principal model systems for analyzing the linkage between dynamics and enzymatic turnover (Arora & Brooks, 2007;Hanson et al 2007;Nagarajan et al 2011;Schrank et al 2009;Shapiro et al 2009Shapiro et al , 2000Shapiro & Meirovitch, 2006). In an extensive multi-approach effort, the Kern laboratory has shown that substrate-free Adk from the hyperthermophilic bacterium Aquifex aeolicus samples 'closed like' structures (Henzler-Wildman et al 2007).…”
Section: Adkmentioning
confidence: 99%
“…Adk undergoes a large conformational change in response to ligand binding that shuttles the protein into a closed and active conformation where phosphoryl transfer occurs (Rhoads & Lowenstein, 1968). Because of its favorable properties -specifically, its tendency to yield excellent NMR spectra (Ådén & Wolf-Watz, 2007;Schrank et al 2009), catalysis of a reversible reaction, and large conformational changes (Müller et al 1996;Müller & Schulz, 1992) -Adk has emerged as one of the principal model systems for analyzing the linkage between dynamics and enzymatic turnover (Arora & Brooks, 2007;Hanson et al 2007;Nagarajan et al 2011;Schrank et al 2009;Shapiro et al 2009Shapiro et al , 2000Shapiro & Meirovitch, 2006). In an extensive multi-approach effort, the Kern laboratory has shown that substrate-free Adk from the hyperthermophilic bacterium Aquifex aeolicus samples 'closed like' structures (Henzler-Wildman et al 2007).…”
Section: Adkmentioning
confidence: 99%
“…t 0 obs (1) Here, [X(t)] is the probability density of observing the trajectory X(t), [X(t)] is the probability density of reaching the same observation via a reference dynamics, and the integration X(t) is a path-integral over all continuous functions of X(t) realizable from the system dynamics. The definition of trajectory entropy in eq 1 is in fact the negative of Kullback−Leibler (KL) divergence that represents the extra information required for encoding [X(t)] relative to that for representing [X(t)].…”
Section: ∫ ≡ − X T X T X T X T ( ) [ ( )] Ln [ ( )] [ ( )]mentioning
confidence: 99%
“…Similarly, enzymatic activity is often dependent on conformational changes during their reaction cycles, and it has been established for a few enzymes that the dynamic interconversions between structural microstates are rate-limiting for turnover of substrate molecules (3,4). For instance, the rate of the reaction catalyzed by Escherichia coli adenylate kinase (Adk), is limited by slow reopening of substrate-binding subdomains in the presence of bound nucleotides (5)(6)(7), as illustrated in the following minimal reaction scheme. Here, E refers to Adk, S to substrate, P to product, and superscripts open and closed to Adk in open and closed states (Fig.…”
Section: Introductionmentioning
confidence: 99%